An Effect Of Pressure Bending In Single Mode Optic Fiber On Light Intensity Attenuation - Alfredo Bangkit H Parapat; Solly Aryza; Amani Darma Tarigan (Jurnal Scientia, 2024)
Single-mode optical fibers are widely used in modern communication systems due to their high data transmission capacity and low signal attenuation. However, the physical condition of the optical fiber, such as bending caused by mechanical pressure, can affect transmission performance. This research aims to analyze the effect of pressurized bending on single-mode optical fibers and its impact on the attenuation of transmitted light intensity. Experiments were conducted by varying the bending radius and pressure applied to the optical fiber to measure changes in the received light intensity. The results show that as the bending radius decreases and the applied pressure increases, the attenuation of light intensity increases significantly. The reduction in light intensity occurs due to the leakage of light modes from the fiber core as a result of physical deformation in the fiber structure. These findings are important for designing more efficient and resilient optical fiber installations, especially in environments prone to physical pressure and bending.